Comparison of time consumption and harvesting cost between manual harvesting (CHISEL) and Mechanized harvesting (CKAT): a case study / Muhammad Mustaqim Jaafar - Jaafar, Muhammad Mustaqim (Faculty of Plantation and Agrotechnology, 2017)
This study was conducted in the various oil palm site owned by smallholder located in Bukit Lintang, Melaka. The collection of data for comparison between manual harvesting technique by using a chisel and mechanized harvesting technique by using CKAT was gathered through record the time taken of harvesting fresh fruit bunches, the cost of harvesting and the number of fresh fruit bunches productivity. The different parameters were assessed for each harvesting technique and a comparison was carried out to decide which harvesting technique that can give more benefit to harvester in order to fulfill harvesting task. Data collection for comparison between manual harvesting technique and mechanized harvesting technique was taken for a month. Trials carried out on manual harvesting technique by using chisel shows that effective working hour per hectare is 1.64 hr ha-1 and effective working hour per hectare for mechanized harvesting technique is 1.84 hr ha-1. Moreover, time taken to cut a bunch for manual harvesting technique is 0.38 min FFB-1 and time taken to cut a bunch for mechanized harvesting technique is 0.43 min FFB-1. The average fresh fruit bunches per hour for manual harvesting technique is 156 FFB hr-1 and average fresh fruit bunches per hour for mechanized harvesting technique is 138 FFB hr-1. Furthermore, the cost per ton for manual harvesting technique is RM 22.35 and cost per ton for mechanized technique is RM 24.05. The study concluded that manual mechanized technique was well accepted because its comfortable handling, ease the process of harvesting and give a lot benefit compared to mechanized harvesting technique